Transformer Fault Diagnosis Based on Multi-Strategy Enhanced Dung Beetle Algorithm and Optimized SVM - Shuming Zhang; Hong Zhou (Energies)
Accurate fault diagnosis of transformers is crucial for preventing power system failures and ensuring the continued reliability of electrical grids. To address the challenge of low accuracy in transformer fault diagnosis using support vector machines (SVMs), an enhanced fault diagnosis model is proposed, which utilizes an improved dung beetle optimization algorithm (IDBO) to optimize an SVM. First, based on dissolved gas analysis (DGA), five characteristic quantities are selected as input features. Second, improvements to the DBO algorithm are made by incorporating Chebyshev chaotic mapping, a golden sine strategy, and dynamic weight coefficients for position updates. The performance of the IDBO is validated using four benchmark test functions, demonstrating faster convergence. Subsequently, the IDBO optimizes the SVM’s penalty factor C and kernel function parameter g, which are then input into the SVM for training, yielding an efficient fault diagnosis model. Finally, comparisons with other methods confirm the usefulness of the proposed model. Experimental results demonstrate that the IDBO–SVM model attains accuracy improvements of 1.69%, 8.47%, and 10.17% over dung beetle optimization–SVM (DBO–SVM), sparrow search algorithm–SVM (SSA–SVM), and grey wolf optimization–SVM (GWO–SVM) models, respectively. In addition to higher accuracy, the IDBO–SVM model also delivers a faster runtime, further highlighting its superior performance in transformer fault diagnosis. The proposed model has practical significance for enhancing the stability of transformer operation.